Bimbingan Motorik Anak Meleui Senam Sehat Di TK Al- Karimah Pekanbaru - Melvi Lesmana Alim; Joni Joni; Jesi Alexander Alim; Rizki Amalia; Suparmi Suparmi (Jurnal Pengabdian Masyarakat (ABDIRA), 2023)
Al-Karimah Kindergarten (TK) Is one of the kindergarten schools in the handsome sub-district of Pekanbaru City. The number of children participating in healthy exercise is 25 people, this is due to maintaining their health after the pandemic. the implementation of children's motor guidance service activities through healthy gymnastics at Al-Karimah Kindergarten Pekanbaru aims to improve children's motor skills through healthy gymnastics. This service is carried out through the Hero University research and community service center in collaboration with the principal of the Al-Karimah Kindergarten. The results obtained by this activity are through healthy gymnastic movements that can improve the motor skills of children in Al-Karimah Kindergarten. And can help teachers in solving problems that exist in kindergarten.